Analisis Persepsi Masyarakat Mengenai Limbah Peternakan Babi di Dusun Gancahan VIII, Sidomulyo, Godean, Sleman - Laire Sukma Arti Suci; Septina Lumbantobing; Zacqy Mahendra Yudha Supriyanto; Dhimas Aditya Prayoga (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study aims to compare the perceptions of pig farmers and non-farmers in Gancahan VIII Hamlet. The research method employed observation, interviews, and literature studies. The results showed that pig farming causes environmental problems, such as odors and dirty irrigation channels, which create a negative perception within the community. Additionally, pig farmers lack care for the waste they produce. The lack of support from relevant agencies regarding pig farm waste management also worsens the environmental impact. However, harmonious intercommunity relations led the community to downplay the perceived environmental impacts through community deliberations regarding complaints about the environmental impacts generated by pig farms.